Apat na screenplay - Garcia, fanny A.; Lao, Armando (Pasig City : Anvril Pub, 1997)
Contents.-- MAricris Sioson : Japayuki / Lualhati Bautista.--Tayong dalawa / Jose Y. dalisay, Jr.-- saan darating ang umaga? / fanny A. Garcia.--Takaw-tukso / Armando Lao.
Keywords: Motion picture play